INEQUALITY IN THE MONETARY AND FUNCTIONINGS SPACES: THE CASE OF PERU UNDER THE FIRST GARCIA GOVERNMENT (1985–1990). (12th August 2011) - Burchi, Francesco; Passacantilli, Andrea
Abstract In this article, we analyze inequality changes in Peru under the first Garcia government (1985–1990). Our findings indicate that stability in consumption inequality and a substantial decline in wealth inequality were achieved, probably thanks to the government's demand‐led policies, despite their deleterious effects on other macroeconomic indicators. The following analysis reveals that inequality in most functionings, including overall well‐being, diminished, as did geographical disparities. We thus offer here (i) a methodological contribution to the debate on inequality, stressing the need to go beyond consumption/income inequality if one wants to track inequality changes across time, and (ii) a contribution to the debate about the socioeconomic situation in Peru between 1985 and 1990. Copyright © 2011 John Wiley & Sons, Ltd.